The Financial Impact of Cultural Diversity on Multinational Firms - Zhang, Fan (John) (Auckland University of Technology, 2018)
This thesis investigates the influence of cultural diversity within U.S. multinational firms on their performance, capital structure, and dividend policy. While existing literature has documented that formal institutions and regulations affect multinational firms, less attention has been paid to the influence of culture. However, culture is important because cultural diversity is an inherent characteristic of multinational firms. During their overseas expansions, multinational firms establish subsidiaries in different countries where cultures differ from one another. Further, according to North (1990) and Williamson (2000), culture affects financial activities either through the daily routines of individuals’ behavior or countries’ overall value systems. Therefore, cultural diversity can significantly influence corporate strategy, operating efficiency and the financial aspects of multinational firms. To investigate the effects of cultural diversity, first, we need to understand what culture is. Chapter 2 provides this background information, which includes definitions and characteristics of culture. Further, there are substantial cross-cultural differences in financial activities and outcomes and Chapter 2 looks into how cultural traits and cultural distances cause these differences. Finally, based on theoretical foundations established in existing studies, Chapter 2 develops arguments on how cultural diversity affects the financial aspects of multinational firms. Chapter 3 constructs a sample of U.S. listed firms over a ten-year period 2004-2013 and an entropy measure of cultural diversity used throughout this thesis. Empirical analyses are carried out starting from Chapter 4, which investigates the impact of cultural diversity on the value of multinational firms. The results in Chapter 4 show that there is a significant and negative relation between cultural diversity and firm value. This negative relation holds after controlling for the firm-level factors, economic treaties, and macroeconomic risks. The negative valuation effect of cultural diversity becomes stronger when controlling for shared language, shared law, and colonial relations, indicating that the effect of cultural diversity is distinctive and not a proxy for these country-level similarities. Further, the negative relation between cultural diversity and firm value does not disappear after using alternative culture and valuation measures. Finally, the negative effect of cultural diversity on firm value is robust over time and to endogeneity tests, suggesting that the result is not driven by the business cycle and that the relation between cultural diversity and firm value is causal. These results support the idea that global diversification negatively affects firm value (Denis et al. 2002). Chapter 4 extends this idea by showing that this valuation effect is associated with the cultural diversity of multinational firms. Chapter 5 examines the impact of cultural diversity on the capital structure of multinational firms. The results show that cultural diversity is negatively related to book and market leverage ratios after controlling for firm-level determinants, country-level factors, and macroeconomic variables. Further, these results are robust to alternative cultural measures, different periods, and endogeneity. The results provide complementary evidence to multinational capital structure studies, in particular to Desai et al. (2008) who show how foreign expansion risk affects the leverage ratios of multinational firms. Therefore, the results suggest that both formal and informal institutional variables are important for determining leverage ratios in a multinational setting. Moreover, Chapter 5 looks into the channels through which cultural diversity reduces leverage ratios and finds that lower leverage ratios associated with higher degrees of cultural diversity are mainly caused by equity issuance rather than debt reduction. These results are in line with Vijh (2006) who finds that firms with parent-subsidiary structures tend to issue equity and Myers (2000) who documents that complex firms are more likely to conduct equity activities. Chapter 5 demonstrates that cultural diversity is related to firm complexity and therefore is a relevant factor in managerial decision-making on the capital structures of multinational firms. Chapter 6 investigates the relation between cultural diversity and the dividend policies of U.S. multinational firms. Specifically, this chapter examines the effect of cultural diversity in the context of the outcome and substitute of agency models. The results show that the effect of cultural diversity on dividend ratios is negative and significant, after controlling for the determinants of dividend decisions documented in prior research. The negative effects of cultural diversity are robust to alternative cultural measures, alternative estimation techniques, as well as a range of subsample analyses. Further analyses show that the effect of cultural diversity is not related to factors that may be associated with dividend decisions in international operations. Therefore, Chapter 6 provides evidence supporting the substitute model that shareholders of U.S. multinational firms with higher cultural diversity concern less about agency problems and therefore accept a lower dividend payout ratio. In conclusion, multinational firms inherently differ from purely domestic firms as their operating environment is more complex. Financial performance, activities, and policies of multinational firms are influenced not only by firm characteristics but also by cultural challenges. However, so far the effect of culture is largely neglected in existing studies. By focusing on cultural diversity and its effects on financial aspects of multinational firms, this thesis fills several important research gaps in the existing literature.
Keywords: Culture; Cultural diversity; Multinational firms; Firm value; Firm performance; Capital structure; Leverage; Debt; Equity; Dividend; Payout; Globalization; Internationalization